The Effectiveness of the Games Approach on Learning Outcome of the Squat Style Long Jump in Elementary School Students Gender-Based - Rukmini Rukmini; Hartati Hartati; Meirizal Usra (AL-ISHLAH: Jurnal Pendidikan, 2023)
The research objective was to determine the effectiveness of the game approach on the learning outcomes of Squat Style Long Jump. The type of research used was quantitative with the true experimental design method. The population in this study amounted to 49 students, with a random sampling technique. Data was collected using tests. Data analysis in this study consists of tests for normality, homogeneity, homogeneity tests for the variance-covariance / box – M matrix, multicollinearity tests, and hypotheses. The results of the research based on testing using the SPSS application show that the experimental group's score is better than the control group simultaneously and partially based on the pretest posttest, which shows a significance value of 0.05, meaning that the playing approach used in this study can improve learning outcomes of Squat Style Long Jump and demonstrate its effectiveness by a score of 75 from students who have joined the experimental group. The teacher can use the result of the study as guidance for long jump learning.